Daratumumab, Bortezomib, Lenalidomide, and Dexamethasone for Multiple Myeloma - Sonneveld, Pieter; Dimopoulos, Meletios A; Boccadoro, Mario; Quach, Hang; Ho, P Joy; Beksac, Meral; Hulin, Cyrille; Antonioli, Elisabetta; Leleu, Xavier; Mangiacavalli, Silvia; Perrot, Aurore; Cavo, Michele; et al. (The New England journal of medicine, 2024)
BACKGROUND: Daratumumab, a monoclonal antibody targeting CD38, has been approved for use with standard myeloma regimens. An evaluation of subcutaneous daratumumab combined with bortezomib, lenalidomide, and dexamethasone (VRd) for the treatment of transplantation-eligible patients with newly diagnosed multiple myeloma is needed. METHODS: In this phase 3 trial, we randomly assigned 709 transplantation-eligible patients with newly diagnosed multiple myeloma to receive either subcutaneous daratumumab combined with VRd induction and consolidation therapy and with lenalidomide maintenance therapy (D-VRd group) or VRd induction and consolidation therapy and lenalidomide maintenance therapy alone (VRd group). The primary end point was progression-free survival. Key secondary end points were a complete response or better and minimal residual disease (MRD)-negative status. RESULTS: At a median follow-up of 47.5 months, the risk of disease progression or death in the D-VRd group was lower than the risk in the VRd group. The estimated percentage of patients with progression-free survival at 48 months was 84.3% in the D-VRd group and 67.7% in the VRd group (hazard ratio for disease progression or death, 0.42; 95% confidence interval, 0.30 to 0.59; P<0.001); the P value crossed the prespecified stopping boundary (P = 0.0126). The percentage of patients with a complete response or better was higher in the D-VRd group than in the VRd group (87.9% vs. 70.1%, P<0.001), as was the percentage of patients with MRD-negative status (75.2% vs. 47.5%, P<0.001). Death occurred in 34 patients in the D-VRd group and 44 patients in the VRd group. Grade 3 or 4 adverse events occurred in most patients in both groups; the most common were neutropenia (62.1% with D-VRd and 51.0% with VRd) and thrombocytopenia (29.1% and 17.3%, respectively). Serious adverse events occurred in 57.0% of the patients in the D-VRd group and 49.3% of those in the VRd group. CONCLUSIONS: The addition of subcutaneous daratumumab to VRd induction and consolidation therapy and to lenalidomide maintenance therapy conferred a significant benefit with respect to progression-free survival among transplantation-eligible patients with newly diagnosed multiple myeloma. (Funded by the European Myeloma Network in collaboration with Janssen Research and Development; PERSEUS ClinicalTrials.gov number, NCT03710603; EudraCT number, 2018-002992-16.).
Keywords: Bortezomib; protokoly protinádorové kombinované chemoterapie; bortezomib; Antibodies, Monoclonal; monoklonální protilátky; lenalidomid; lidé; Multiple Myeloma; progrese nemoci; mnohočetný myelom; Lenalidomide; dexamethason; Disease Progression; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Humans